1997
DOI: 10.1007/s004600050353
|View full text |Cite
|
Sign up to set email alerts
|

Electron scattering on C6F6 and SF6 molecules

Abstract: Total absolute cross sections for electron scattering on hexafluorobenzene, C 6 F 6 , and sulfur hexafluoride, SF 6 , molecules, have been measured as a function of impact energy from 0.6 to 250 eV. The total cross section for C 6 F 6 exhibits a very broad peak stretching from 10 to 100 eV with some weak features near 9.5 and 15 eV superimposed on the peak. Apart from the well-known low-energy resonant structures in the SF 6 total cross section function, a new weak resonant feature close to 25 eV has been noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 38 publications
7
18
0
Order By: Relevance
“…It is also worth noting that the share of ionization processes in the scattering for 1,3-C 4 F 6 is, like for other perfluorides, relatively low, and around the maximum of the total ionization cross section amounts to no more than 1/3 of the TCS (cf figure 1). It is interesting to note that above 3 eV the general shape of the TCS energy function for the 1,3-C 4 F 6 compound closely resembles those found for C 2 F 4 [48] and for C 6 F 6 [50]. The ratio of TCS values is about 1:1.6:2 for C 2 F 4 , 1,3-C 4 F 6 and C 6 F 6 , respectively.…”
Section: Resultssupporting
confidence: 66%
“…It is also worth noting that the share of ionization processes in the scattering for 1,3-C 4 F 6 is, like for other perfluorides, relatively low, and around the maximum of the total ionization cross section amounts to no more than 1/3 of the TCS (cf figure 1). It is interesting to note that above 3 eV the general shape of the TCS energy function for the 1,3-C 4 F 6 compound closely resembles those found for C 2 F 4 [48] and for C 6 F 6 [50]. The ratio of TCS values is about 1:1.6:2 for C 2 F 4 , 1,3-C 4 F 6 and C 6 F 6 , respectively.…”
Section: Resultssupporting
confidence: 66%
“…It is worth noting that the qualitative behaviour of the TCS in the low-energy part of energy dependence for cyclopropane resembles that for another cyclic hydrocarbon benzene (Możejko et al 1996) and, to some extent, that for hexafluorobenzene (cf Kasperski et al 1997).…”
Section: Cyclopropanementioning
confidence: 89%
“…In recent years, various theoretical and experimental investigations of electron-impact scattering by SF 6 have been reported by different groups owing to this molecule's environmental impact and considerable applications in industry as discussed earlier. Makochekanwa et al, 8 Dababneh, 9 Kennerlya et al, 10 Kasperski et al, 11 Zecca et al, 12 Wan et al, 13 Ferch et al, 14 Trajmar et al, 15 Limão-Vieira et al 16 and Rohr 17 measured total cross sections of electron impact on SF 6 , while Cho et al, 18 Srivastava et al, 19 Johnstone and Newell 20 and Sakae et al 21 reported the experimental differential and integral elastic cross sections. Benedict and Gyemant 22 calculated electron impact total elastic cross sections using a multiple scattering method.…”
Section: Introductionmentioning
confidence: 99%